Enhanced Adsorption of Brilliant Green Dye Using Barium Ferrite/Graphene Oxide Nanocomposites - Usama Akram Saed; Alaa H. Ali; Ammar A. Saoud; Zeyad Zeitoun (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study presents the synthesis and characterization of barium ferrite/graphene oxide (BaFeO/GO) nanocomposites for the adsorption of brilliant green dye (BGD) from aqueous solutions. BaFeO/GO nanocomposites were fabricated via a co-precipitation method with varying GO content (10-30 wt%), and characterized using Fourier Transform Infra rEd (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Field-Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscope (TEM), Brunauer, Emmett, and Teller (BET), and Vibrating Sample Magnetometer (VSM) techniques. The incorporation of GO enhanced the surface area, reduced BaFeO nanoparticle agglomeration, and introduced additional oxygen-containing functional groups, significantly improving the adsorption performance. Batch adsorption experiments were conducted to evaluate the effects of pH, contact time, adsorbent dose, and initial dye concentration. The maximum dye removal efficiency reached 98.9% with the BaFeO/30%GO composite. Kinetic studies showed excellent agreement with the pseudo-second-order model, while adsorption isotherm analysis indicated that the Langmuir model best fit the equilibrium data, suggesting monolayer adsorption. These results demonstrate the potential of BaFeO/GO nanocomposites as efficient, magnetically separable adsorbents for the removal of cationic dyes from wastewater. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).